2007
DOI: 10.1152/ajpendo.00463.2006
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids induce MMP-9 expression through RARα during mammary gland remodeling

Abstract: Retinoic acid (RA) is a signaling molecule in the morphogenesis of the mammary gland, modulating the expression of matrix metalloproteinases (MMPs). The aim of this paper was to study the role of RA during weaning, which consists of three events: apoptosis of the secretory cells, degradation of the extracellular matrix, and adipogenesis. CRABP II and CRBP-1 carrier proteins increased significantly during weaning compared with lactating glands but reverted to control values after the litter resuckled. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 33 publications
4
45
0
Order By: Relevance
“…As we know, ATRA interacts specifically with the RARs and RXRs, and most of the retinoic acid receptor subtypes are expressed in kidney, especially RAR-α and RAR-β [28]. A study has shown that ATRA induced the expression of MMP-9 through RAR-α during mammary gland remodeling [29]. Little is known about the promotor elements involved in MMP-2 and TIMP-1 regulation by ATRA, but we assume that a direct action of retinoic acid receptors is operative here as well.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, ATRA interacts specifically with the RARs and RXRs, and most of the retinoic acid receptor subtypes are expressed in kidney, especially RAR-α and RAR-β [28]. A study has shown that ATRA induced the expression of MMP-9 through RAR-α during mammary gland remodeling [29]. Little is known about the promotor elements involved in MMP-2 and TIMP-1 regulation by ATRA, but we assume that a direct action of retinoic acid receptors is operative here as well.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin from mammary tissue was fixed and immunoprecipitated as described previously. 3,38 The following antibodies from Santa Cruz Biotechnology (Santa Cruz, CA, USA) were used: p65 (sc-109), p300 (sc-585) and RNA pol II (sc-899). After DNA purification, Input, Immunoprecipitated and Unrelated Ab fractions were analyzed by PCR with specific primers for either Real-time quantitative PCR (RT-qPCR) analysis and reverse transcriptase (RT)-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the response of the proteolytic status to VAD might be tissue specific. One fact favours this possibility: opposing results have been reported on the effect of RA in the expressions of MMP2 and 9 by different cell types in culture or tissues in vivo [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%